Chromogranin A and Its Fragments in the Critically Ill: An Expanding Domain of Interest for Better Care - Francis Schneider; Raphaël Clère-Jehl; Francesco Scavello; Thierry Lavigne; Angelo Corti; Tommaso Angelone; Youssef Haïkel; Philippe Lavalle (Pharmaceutics, 2022)
Life-threatening diseases challenge immunity with a release of chromogranins. This report focuses on Chromogranin A (CGA) and some of its derived peptides in critically ill patients, with attention paid to their potential to become biomarkers of severity and actors of defense. First, we studied whether circulating CGA may be a biomarker of outcome in non-selected critically ill patients: CGA concentrations were reliably associated with short-term death, systemic inflammation, and multiple organ failure. Additionally, when studying Vasostatin-I, the major N-terminal fragment of CGA, we noted its reliable prognostic value as early as admission if associated with age and lactate. In trauma patients, CGA concentrations heralded the occurrence of care-related infections. This was associated with an in vitro inhibitor impact of Chromofungin on both NF-kappa B- and API-transcriptional activities. Secondly, in life-threatening disease-induced oxidative stress, the multimerization of Vasostatin-I occurs with the loss of its anti-microbial properties ex vivo. In vivo, a 4%-concentration of non-oxidized albumin infusion reversed multimerization with a decrease in care-related infections. Finally, in vitro Catestatin impacted the polymorphonuclear cells-Ca++-dependent, calmodulin–regulated iPLA2 pathway by releasing immunity-related proteins. Furthermore, human Cateslytin, the active domain of Catestatin, helped destroy S. aureus: this prompted the creation of synthetic D-stereoisomer of CGA-derived peptides against superbugs for the protection of implanted devices. In conclusion, CGA consideration in the critically ill is only starting, but it offers interesting perspectives for improved outcomes.